Survival of Antarctic Cryptoendolithic Fungi in Simulated Martian Conditions On Board the International Space Station - Onofri, Silvano; de Vera, Jean Pierre Paul; Zucconi, Laura; Selbmann, Laura; Scalzi, Giuliano; Venkateswaran, Kasthuri J.; Rabbow, Elke; de la Torre, Rosa; Horneck, Gerda (Astrobiology, 2015)
Dehydrated Antarctic cryptoendolithic communities and colonies of the rock inhabitant black fungi Cryomyces antarcticus (CCFEE 515) and Cryomyces minteri (CCFEE 5187) were exposed as part of the Lichens and Fungi Experiment (LIFE) for 18 months in the European Space Agency's EXPOSE-E facility to simulated martian conditions aboard the International Space Station (ISS). Upon sample retrieval, survival was proved by testing colony-forming ability, and viability of cells (as integrity of cell membrane) was determined by the propidium monoazide (PMA) assay coupled with quantitative PCR tests. Although less than 10% of the samples exposed to simulated martian conditions were able to proliferate and form colonies, the PMA assay indicated that more than 60% of the cells and rock communities had remained intact after the “Mars exposure.” Furthermore, a high stability of the DNA in the cells was demonstrated. The results contribute to assessing the stability of resistant microorganisms and biosignatures on the surface of Mars, data that are valuable information for further search-for-life experiments on Mars.